NIGERIA/BIAFRA CIVIL WAR: MY EXPERIENCE/ Achike Udenwa - Osakwe, Chukwuma (Scientia Militaria - South African Journal of Military Studies, 2013)
This book has seven chapters covering aspects of Nigeria’s history, the author’s experience during the Civil War, 1967–1970 and his reflection on Nigeria as a nation. The purpose of the book as the author makes clear is “to fill the gap and further highlight the role played by the lower command – the platoons, companies, battalions and brigades etc.”. Finally, and among others, it is the story of how young officers without professional training, but consumed with patriotic fervour, fought in a war.